Influence of rolling speed during hot forming using HDQT-R 30-12 machine on the properties of stainless steel 08Ch18N10T. Issue 1 (August 2021) - Jirkova, H; Janda, T; Peković, M; Říha, J; Mach, J; Krsová, D
Abstract: Mechanical properties of austenitic stainless steels can be improved by a suitable combination of forming and heat treatment operations. In addition to rolling reduction and speed, the heat treatment parameters are very important as well. Heat treatment typically combines solution and stabilization annealing. In components of WWER nuclear reactors, most of which are made of these steels, it is necessary to achieve the prescribed hot mechanical properties. Bars of 30 mm diameter made of titanium stabilized 08Ch18N10T steel were rolled in an incremental rolling machine. After induction heating to 950°C, different roll speeds were used, from 200 rpm to 25 rpm. The rolled bars were cooled in water and stabilization annealed at 720°C for 10 hours or at 800°C for 1 hour. Mechanical properties were determined by tensile testing at room temperature and at 350°C. Slower rolling speeds led to lower elongation (40%) than the faster ones (50%). Metallographic evaluation focused on the effect of forming on the grain size.